Whole genome sequencing and bulked segregant analysis suggest a new mechanism of amitraz resistance in the citrus red mite, Panonychus citri (Acari: Tetranychidae). Issue 11 (21st July 2021) - Yu, Shi‐Jiang; Cong, Lin; Pan, Qi; Ding, Li‐Li; Lei, Shuang; Cheng, Lu‐Yan; Fang, Yun‐Hong; Wei, Zhi‐Tang; Liu, Hao‐Qiang; Ran, Chun
Abstract: BACKGROUND: Amitraz is a broad‐spectrum insecticide/acaricide for the control of aphids, psyllids, ticks and mites. Current evidence suggests that ticks and phytophagous mites have developed strong resistance to amitraz. Previous studies have shown that multiple mechanisms are associated with amitraz resistance in ticks, but very few reports have involved Panonychus citri . We therefore used whole genome sequencing and bulked segregant analysis (BSA) to identify the mechanism underlying P. citri 's resistance to amitraz. RESULTS: High‐quality assembly of the whole P. citri genome was completed, resulting in a genome of approximately 83.97 Mb and a contig N50 of approximately 1.81 Mb. Gene structure predictions revealed 11 577 genes, of which 10 940 genes were annotated. Trait‐associated regions in the genome were mapped with bulked segregant analysis and 38 candidate SNPs were obtained, of which T752C had the strongest correlation with the resistant trait, located at the 5′ untranslated region (UTR) of the β‐2R adrenergic‐like octopamine receptor gene. The mutation resulted in the formation of a short hairpin loop structure in mRNA and gene expression was down‐regulated by more than 50% in the amitraz‐resistant strain. Validation of the T752C mutation in field populations of P. citri found that the correlation between the resistance ratio and the base mutation was 94.40%. CONCLUSION: Our results suggest that this 5′ UTR mutation of the β‐2R octopamine receptor gene, confers amitraz resistance in P. citri . This discovery provides a new explanation for the mechanism of pest resistance: base mutations in the 5′ untranslated region of target gene may regulate the susceptibility of pests to pesticides. Abstract : 5′ UTR mutation of the β‐2R octopamine receptor gene confers amitraz resistance in Panonychus citri. © 2021 Society of Chemical Industry.